2008
DOI: 10.1007/s10753-008-9094-y
|View full text |Cite
|
Sign up to set email alerts
|

Ceftiofur Regulates LPS-Induced Production of Cytokines and Improves LPS-Induced Survival Rate in Mice

Abstract: The influence of ceftiofur on immune responses has been suggested by results of in vitro studies. This effect was studied using a murine model that measured mortality and early cytokine responses after challenge with endotoxin. To investigate the treatment of endotoxic mice with ceftiofur, mice were pretreated with ceftiofur at different times before and after challenge with a lethal dose of 30 mg/kg lipopolysaccharide (LPS). We found that 20 mg/kg ceftiofur had a significant protective effect and reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…LPS induces rapid phosphorylation of ERK1/2, JNK, and p38 kinase in a macrophage cell line (RAW264.7), and ceftiofur treatment impairs phosphorylation of these molecules in a dose-dependent manner [14] . This in vitro effect of ceftiofur in cell culture was previously confirmed by LPS-induced endotoxemia and acute lung injury animal models in mice in vivo as well [15,16] . We also examined that, parallel to its inhibitory effect on increased protein expression in the spinal cord, ceftiofur significantly attenuated clinical signs in a rat neuropathic pain model in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…LPS induces rapid phosphorylation of ERK1/2, JNK, and p38 kinase in a macrophage cell line (RAW264.7), and ceftiofur treatment impairs phosphorylation of these molecules in a dose-dependent manner [14] . This in vitro effect of ceftiofur in cell culture was previously confirmed by LPS-induced endotoxemia and acute lung injury animal models in mice in vivo as well [15,16] . We also examined that, parallel to its inhibitory effect on increased protein expression in the spinal cord, ceftiofur significantly attenuated clinical signs in a rat neuropathic pain model in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 61%
“…Ceftiofur is a third-generation cephalosporin derivative and inhibits lipopolysaccharide (LPS)-induced production of TNF-α, IL-1β, and IL-6 in mouse macrophages through the inhibition of the LPSinduced activation of MAPK signaling and LPS-induced translocation of NF-κB from the cytoplasm to the nucleus [14] . It also has beneficial effects on LPS-induced endotoxemia and acute lung injury in mice through modulation of cytokine levels [15,16] .…”
mentioning
confidence: 99%
“…Our laboratory has recently reported that ceftiofur exerts its antiinflammatory activity by blocking the NF-κB pathway in LPS-induced RAW 264.7 macrophages and improves survival in murine endotoxemia [12,27]. While, NF-κB activity was not assessed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…It has been documented that this immunosuppressive potential of ceftiofur may be beneficial in resolving bacterial infection. Ceftiofur pretreatment of mice subsequently challenged by LPS significantly decreased plasma levels of tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and IL-6 compared to mice treated with LPS alone (7). According to the authors, downregulation of pro-inflammatory cytokines by ceftiofur decreases mortality in LPS-challenged mice.…”
Section: Discussionmentioning
confidence: 99%